MODEL LATIHAN INTERCEPT UNTUK PEMAIN BELAKANG DALAM PERMAINAN SEPAK BOLA USIA 15 TAHUN - Achmad Syarip Lokanugraha (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2021)
The aim of this research and development is for the Intercept Exercise Model for Defenders in 15-Year-Old Soccer Games. Research & Development (R & D) development research from Borg and Gall. The stages in this research and development are, in stages: (1) needs analysis, (2) expert evaluation (initial product evaluation); (3) limited testing (small group trials); (4) main testing (field testing), (5) Test the effectiveness of the model. The effectiveness test uses an intercept test for a defender in a soccer game at the age of 15 years. Analysis of research data using the T test with a significance level of 0.05. Data analysis was obtained by the average value of four skills data that the difference in ability to intercept: pre test 3,154 and posttest 1,743, pretest control class: 3,204 and posttest3,620. Then the intercept training model for defenders in a 15-year-old violin game. Based on the results of the development it can be concluded that: (1) The final product in the form of an intercept training model for defenders in a 15-year-old soccer game for a 15-year-old soccer school consisting of 30 training model items. (2) An intercept training model for defenders in a 15-year-old soccer game is effective for increasing intercept ability for defenders in soccer games because the training model varies and matches the needs of the actual game, so the training process does not go monotonous and boring. Abstrak Tujuan dari penelitian dan pengembangan ini adalah untukmengembangkan Model Latihan Intercept untuk Pembela di Pertandingan Sepakbola Berusia 15 Tahun. Metode yang digunakandalampenelitianiniyaituRnDdari Borg and Gall. Tahapan dalam penelitian dan pengembangan ini adalah: (1) analisis kebutuhan, (2) evaluasi ahli (evaluasi produk awal); (3) pengujian terbatas (uji coba kelompok kecil); (4) pengujian utama (pengujian lapangan), (5) Uji efektivitas model. Tes efektivitas menggunakan tes intersepsi untuk pemain bertahan dalam pertandingan sepak bola pada usia 15 tahun. Analisis data penelitian menggunakan uji T dengan tingkat signifikansi 0,05. Analisis data diperoleh dengan nilai rata-rata data empat keterampilan bahwa perbedaan kemampuan untuk mencegat: pre test 3,154 dan posttest 1,743, kelas kontrol pretest: 3,204 dan posttest 3,620. Hasil daripenelitianiniyaitu (1) Produk akhir dalam bentuk model pelatihan mencegat untuk pembela dalam pertandingan sepak bola 15 tahun untuk sekolah sepak bola 15 tahun yang terdiri dari 30 item model pelatihan. (2) Model pelatihan intersep untuk pemain bertahan dalam pertandingan sepak bola berusia 15 tahun efektif untuk meningkatkan kemampuan intersep bagi pemain bertahan dalam permainan sepak bola karena model pelatihannya bervariasi dan sesuai dengan kebutuhan permainan sebenarnya, sehingga proses pelatihan tidak berjalan monoton dan membosankan. Kata Kunci : Intercept Training, Sepak Bola